Improved Reconstruction Quality of Bioluminescent Images by Combining SP3 Equations and Bregman Iteration Method. (22nd January 2013) - Wu, Qiang; Feng, Jinchao; Jia, Kebin; Wang, Xiangyu
Abstract : Bioluminescence tomography (BLT) has a great potential to provide a powerful tool for tumor detection, monitoring tumor therapy progress, and drug development; developing new reconstruction algorithms will advance the technique to practical applications. In the paper, we propose a BLT reconstruction algorithm by combining SP3 equations and Bregman iteration method to improve the quality of reconstructed sources. The numerical results for homogeneous and heterogeneous phantoms are very encouraging and give significant improvement over the algorithms without the use of SP3 equations and Bregman iteration method.